OPTIMIZATION OF INTEGRATED MULTI-TROPHIC AQUACULTURE (IMTA) CULTIVATION IN AQUARIA: A REVIEW OF PRODUCTIVITY, ECOSYSTEM BALANCE, AND ENVIRONMENTAL SUSTAINABILITY - Afisha, Fauziyah Nur; Hasan, Zahidah; Iskandar, Iskandar; Haetami, Kiki; Sahidin, Asep; Grandiosa, Roffi (Jurnal Perikanan Unram, 2025)
This study aimed to evaluate the effectiveness of an aquarium-based Integrated Multi-Trophic Aquaculture (IMTA) system compared to a monoculture system. The research was conducted from November to December 2024 at the Aquaculture Laboratory, Faculty of Fisheries and Marine Sciences, Universitas Padjadjaran. The experimental design used was a Completely Randomized Design (CRD) with five treatments and three replications, involving combinations of guppy fish (Poecilia reticulata), Egeria densa aquatic plants, Ramshorn snails (Planorbella duryi), and Orange Rili shrimp (Neocaridina davidi). Parameters observed included water quality (pH, DO, nitrate, phosphate, turbidity, temperature), organism growth, benefit-cost ratio (BCR), and aesthetic value using a 1–5 scale. The results showed that Treatment E (combining fish, plants, snails, and shrimp) provided the best performance, with the most stable water quality, highest organism growth, highest BCR, and an average aesthetic score of 4.89. The IMTA system was shown to improve resource efficiency, reduce biological waste, and enhance the visual appeal of aquarium-based aquaculture. These findings support the application of aquarium-scale IMTA as a sustainable aquaculture model that is ecologically, economically, and aesthetically adaptive.